2018
DOI: 10.3892/mmr.2018.9373
|View full text |Cite
|
Sign up to set email alerts
|

Immune thrombocytopenia induces autophagy and suppresses apoptosis in megakaryocytes

Abstract: Immune thrombocytopenia (ITP) is the main pathogenesis of excessive platelet destruction and abnormal megakaryocyte apoptosis, however, the mechanism underlying this abnormality in megakaryocytes remains to be elucidated. Since autophagy and apoptosis are closely interrelated, it can be speculated that the abnormal apoptosis of ITP megakaryocytes is associated with autophagy. To test this hypothesis, a total of 14 patients with ITP and 23 healthy controls were recruited. MEG‑01 cell line was cultured in vitro,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
(26 reference statements)
2
6
0
Order By: Relevance
“…The data above collectively revealed an abnormal Beclin-1 immunoregulation; therefore, downregulating the expression of Beclin-1 in ITP patients might also represent a therapeutic approach against ITP. Liu et al found that ITP plasma induced inhibition of megakaryocyte apoptosis, resulting in decreased activation of caspase-3, leading to an increase in Beclin-1, 28 which verified our experimental results.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The data above collectively revealed an abnormal Beclin-1 immunoregulation; therefore, downregulating the expression of Beclin-1 in ITP patients might also represent a therapeutic approach against ITP. Liu et al found that ITP plasma induced inhibition of megakaryocyte apoptosis, resulting in decreased activation of caspase-3, leading to an increase in Beclin-1, 28 which verified our experimental results.…”
Section: Discussionsupporting
confidence: 91%
“…Studies found that ITP plasma induced autophagy and suppressed apoptosis in megakaryocytes. The inhibition of megakaryocyte apoptosis could result in impaired platelet release and reduced circulating platelets 28,38 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion deserves further research. For example, current results need more case validation analyses, functional verification assays and larger population-based studies to confirm [103]. And this conclusion is in contrast to our treatment of ITP autophagy induced by rapamycin.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 91%
“…However, the study of Liu et al demonstrated that the plasma in ITP patients induces autophagy and suppresses apoptosis [103]. And the inhibition of autophagy may be a novel treatment in further investigation.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%